(untitled) (Innovative Teaching and Learning Journal, 2025)
Living sustainably requires a paradigm shift toward empowering individuals and communities through effective knowledge transfer and engagement. This study presents a structured framework for the UUM@Community STEM Sustainability Program, utilizing a service-learning approach to promote awareness of selected sustainable development goals (SDGs). The framework was developed using the Design and Development Research (DDR) approach, encompassing stages of Analysis, Design, Development, Implementation, and Evaluation. A personalized dashboard was created to monitor program effectiveness, allowing for continuous improvement through feedback and data analytics. Findings demonstrate the framework’s capacity to enhance community engagement and empower participants through structured processes and digital tools. The study contributes to the body of knowledge by providing a replicable framework for technology-assisted community outreach and suggests future enhancements such as integrating AI-powered tools and expanding collaboration networks.